Development of laser-induced graphene impedimetric biosensors for Escherichia coli detection - Moreira, Ana Luís Cerqueira Brinca (2021)
In this work, it was intended the development of a laser induced graphene (LIG) impedimetric immunosensor for Escherichia coli detection. This investigation was explored in cooperation with Bosch Thermotechnology S.A. Aveiro within the co-promoted Smart Green Home project. To start, LIG electrodes were produced, fixating all the laser parameters with exception of the laser scan speed, vlaser, for which five values (150, 200, 250, 300 and 350 mm/s) were explored. A comprehensive study to compare the five vlaser was done through Raman spectroscopy, scanning electron microscopy (SEM) and determination of the respective electrochemical parameters: heterogeneous charge transfer rate constant, k0, effective electroactive area, Aeff, and capacitance per unit area, "#. As a result, the sample produced with 250 mm/s was chosen to proceed with functionalisation, being subjected to X-ray photoelectron spectroscopy (XPS). Afterwards, a four steps functionalisation, comprehending hydroxylation, APTES silanization, anti-E.coli covalent immobilisation and BSA passivation, was studied through electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). Particularly, it was explored the need to perform hydroxylation using Raman spectroscopy, XPS and determination of the corresponding k0, Aeff and "#. Also, in the case of APTES silanization, it was relevant to establish the respective k0, Aeff and "# to better understand the EIS and CV measurements. Consequently, a suitable functionalisation protocol was achieved. Lastly, the biosensing response of the produced biosensors was investigated by EIS towards 7 E. coli concentrations (5, 10, 102, 103, 104, 105, 106 CFU/mL). These tests also comprised false-positive and selectivity controls. However, the obtained results were inconclusive regarding E. coli detection, so a set of confirmatory tests was established using two strains of E. coli to verify the efficiency of antibody-antigen interaction. To prove E. coli detection, the biosensors, upon bacteria immobilisation, were submitted to EIS measurements, bacterial DNA tests and SEM analysis. In fact, E. coli detection was confirmed